Portuguese Castanea sativa Genetic Resources: Characterization, Productive Challenges and Breeding Efforts - Megan Braga; Susana de Sousa Araújo; Hélia Sales; Rita Pontes; João Nunes (Agriculture, 2023)
Chestnuts are multipurpose trees that grow mainly in the Northern Hemisphere due to their aptitude for fruit and wood production. These trees are vastly significant for the economy and wildlife. The widespread distribution of these trees demonstrates their genetic adaptability to many environmental conditions. The main varieties of European chestnut (Castanea sativa Miller) cultivated in Portugal, their productive challenges and breeding and biotechnological efforts developed over the last decades are described. This paper highlights the efforts focused on the improvement of varieties and rootstocks through selection and hybridization of European chestnut with the Asian species Castanea crenata Siebold and Zuccarini and Castanea mollissima Blume, which are resistant to ink disease, which have been the foundation of the Portuguese chestnut breeding programs. Breeding and biotechnological efforts developed over the last decades, focused on ink disease and chestnut blight resistance, are described. The potentialities of this research to stimulate the competitiveness of bioeconomy-based knowledge and innovation in the productive chestnut sector is also discussed.